Proliferation of Islamic Ideology Through Print Media: Critical Discourse Analysis of the Columns of ‘The Nation’ Newspaper - Yousuf, Muhammad; Maryam, Wajeeha; Naeem, Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
The researcher focused on how ‘The Nation’, a Pakistani newspaper, imposes its ideology on its readership. Two articles from Pakistan's top English newspaper, The Nation, are used to examine the spread of Islamic ideology among readers to carry out the results and conclusions. The investigation's findings proved that racism is abhorred by Islam. The newspaper "The Nation" also introduced readers to racism. The journal acknowledged racism as a vile social force that is wreaking havoc and bloodshed around the globe. "The Nation" also significantly enhances the Islamic intellectual concept of "human constitutional rights in Islam." There's a growing amount of turmoil happening on Earth. On this matter, nevertheless, prompt action is needed. As the Quran says, "We have been honoured as the youngster and as carried on the land-living and oceans and have equipped them with much better things," Muslims must develop a sense of worth. He wanted them onto a large number of our offspring. The results of the study clearly showed that The Nation, like Islam, has always promoted a very positive view of constitutionally protected human rights.